Association of a cellular heat shock protein with simian virus 40 large T antigen in transformed cells. - Sawai, E T (1989)
The viral oncoprotein of simian virus 40, large T antigen (T-ag), is essential for viral replication and cellular transformation. To understand the mechanisms by which T-ag mediates its multifunctional properties, it is important to identify the cellular targets with which it interacts. A cellular protein of 73 kilodaltons (p73) which specifically associates with T-ag in simian virus 40-transformed BALB/c 3T3E cells has been identified. The binding of p73 to T-ag was demonstrated by coimmunoprecipitation analyses using polyclonal and monoclonal antibodies specific for T-ag. The interaction of p73 with T-ag was independent of T-ag complex formation with the cellular protein p53. Partial V8 protease cleavage maps for p73 and the cellular heat shock protein hsp70 were identical. Immunoblot analyses indicated that p73 complexed to T-ag was antigenically related to hsp70. T-ag deletion mutants were constructed that remove internal, amino-terminal, and carboxy-terminal sequences. These mutants mapped the p73 binding domain to the amino terminus of T-ag. The specific dissociation of p73 from the p73/T-ag complex was mediated by ATP; GTP, CTP, and UTP were also utilized as substrates. These characteristics suggest that p73 may be a member of the hsp70 family of heat shock proteins. The biologic significance of p73/T-ag complex formation has yet to be determined.